A catchment partnership approach to delivering natural flood management in the Evenlode, UK. Issue 7 (24th May 2019) - Old, Joanne; McKnight, David; Bennett, Richard; Grzybek, Roland
Abstract : Adapting to climate change and its impacts on water resources is one of the major challenges facing the UK. In the first scheme of its kind in the Thames basin, this paper describes how natural flood management (NFM) is being piloted in the Littlestock Brook tributary of the Evenlode catchment. This 5-year scheme (2016–2021) explores the delivery mechanisms and assesses the effectiveness of NFM measures to reduce flood risk in Milton-under-Wychwood, improve water quality and create habitat. It has secured £640 000 from Environment Agency programmes, the Thames Regional Flood and Coastal Committee, other partners and landowners. In 2018, ten field corner bunds were created with a combined storage capacity of 26 000 m 3 . Woody dams in the brook divert high flows into these flood storage areas. Critical to success is integrated delivery through the Evenlode Catchment Partnership and engagement of the local community. Catchment partnerships deliver a range of environmental, social and economic benefits, and directly support many of the ambitions under the government's 25-Year Environment Plan and the Water Framework Directive. Collaborative working with Thames Water, the Department for Environment, Food and Rural Affairs, consultants and academics has enabled the project to utilise existing delivery mechanisms and to model and monitor the effectiveness of NFM.